Measurement assisted assembly for high accuracy aerospace manufacturing - Drouot, Adrien; Zhao, Ran; Irving, Lucas; Sanderson, David; Ratchev, Svetan (2018)
Measurement Assisted Assembly is a key concept for the modernisation of aerospace assembly processes, i.e. improving their efficiency while reducing the manufacturing costs. This concept suggests a paradigm shift in the assembly of high-complexity products as it encompasses the development and the use of robotics solutions smartly integrated with innovative measurement technologies. Expected outcomes are, among others, a better positioning accuracy of the components and a significant reduction of the rectification and rework requirements that are usually common with traditional assembly processes, especially but not limited to aerospace manufacturing. To achieve these objectives, a high precision metrology system that automatically inspects and corrects the pose of the robotic manipulators during the assembly operations is of great importance. In this paper, a high-accuracy real-life application of the concept of Measurement Assisted Assembly is presented as a part of the Future Automated Aircraft Assembly Demonstrator developed by the University of Nottingham. Experimentations have shown that, using the production environment described hereafter, a positioning accuracy better than +- 0.1 mm can be achieved for large airframe components.